THE STATUS AND FLUXES OF ALKALI AND ALKALINE-EARTH METALS IN A SAVANNA ALFISOL UNDER LONG-TERM CULTIVATION - Agbenin J.O. (My University, 2001)
Information on the status and fluxes of alkali (Na, K and Rb) and alkaline-earth metals (Ba, Ca, Mg and Sr) in cultivated soils is required to predict their responses and sensitivity to acidification. The soils for this study were fertilized with NPK (NPK-plot), farmyard manure (FYM-plot) and combined application of FYM and NPK (FYM+NPK-plot) for 50 years. A control-plot, which neither received NPK nor FYM for 50 years, and a natural site were also sampled. Compared to the natural site, significant losses of alkali and alkaline-earth metals occurred in NPK-plot. The FYM+NPK-plot gained excess mass of Ca and Mg, but incurred losses of Na, Rb, K, Ba and Sr. In the FYM-plot, 4% excess mass of Mg and 65% excess mass of Ca were added to the soil, while in the FYM+NPK-plot, 18% excess mass of Mg and 61% excess mass of Ca were added to the soil. The excess masses of Ca and Mg added to these plots partly accounted for from incidental additions through FYM and NPK fertilization and from aeolian sources which, together, were accounted for between 40% and 56% of the Ca-enrichment and between 45% and 100% of Mg-enrichment. Evidence in the study supports the notion that sole application of NPK fertilizers leads to chemical degradation and increases the risk of acidification of savanna Alfisols under continuous cultivation.
Keywords: ALFISOL; ALKALINE-EARTH METALS; CULTIVATION; SAVANNA